BUYING CONTACT LENSES ONLINE: AN UNDERGRADUATE STUDENTS’ PERSPECTIVE - Neemit Klinthong Chon; Siti Syamsul Nurin Mohmad Yazam (The Indonesian Journal of Communication Studies, 2015)
The phenomenon of students wearing contact lenses in universities has become a trend as they want to look different from their normal appearance. The prices of contact lenses in optometrists are quite expensive. Therefore, as students with limited source of income, they will try to find another alternative to get the contact lenses at a lesser price. One of the solutions is to purchase contact lenses from online retailers. Thus, by using the Theory of Planned Behaviour by Ajzen, this study was carried out to identify students’ perception in buying contact lenses online. Data was collected by using a questionnaire from 119 undergraduate students. The findings indicated that students have high intention to purchase contact lenses online and mostly are influenced by friends and the mass media.